2012
DOI: 10.2337/dc11-2452
|View full text |Cite
|
Sign up to set email alerts
|

Changing Physical Activity Behavior in Type 2 Diabetes

Abstract: OBJECTIVEBehavioral interventions targeting “free-living” physical activity (PA) and exercise that produce long-term glycemic control in adults with type 2 diabetes are warranted. However, little is known about how clinical teams should support adults with type 2 diabetes to achieve and sustain a physically active lifestyle.RESEARCH DESIGN AND METHODSWe conducted a systematic review of randomized controlled trials (RCTs) (published up to January 2012) to establish the effect of behavioral interventions (compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
231
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(258 citation statements)
references
References 46 publications
(155 reference statements)
10
231
1
7
Order By: Relevance
“…The existing literature on predictors of effective PA interventions SYSTEMATIC REVIEWS [74][75][76]. What remains unclear is how these evidence-based techniques may be optimally implemented with pragmatic approaches in clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on predictors of effective PA interventions SYSTEMATIC REVIEWS [74][75][76]. What remains unclear is how these evidence-based techniques may be optimally implemented with pragmatic approaches in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Other review articles have lamented the lack of data on fidelity of intervention delivery in RCTs and have noted this as a limitation to identifying key moderators of PA interventions [76]. The highly pragmatic and effective intervention by Di Loreto et al that we studied in the present review balanced the competing clinical demands and fidelity to intervention techniques by condensing several effective behavioral change techniques into a simple yet tailored counseling checklist which identified enjoyable and appropriate PA options at the individual level and encouraged patients to continue with these programs through the use of social support, problem-solving, and PA tracking [45].…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 review and meta-analysis by Avery et al [12] found behavioural interventions aimed at increasing physical activity in adults with type 2 diabetes produced significant increases in physical activity in addition to significant improvements in BMI and HbA1c. Guidelines now exist on the development of physical activity interventions for adults with type 2 diabetes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews of the literature have explored the effectiveness of 1 these factors with various findings. Significant improvements in glycaemic control are associated with interventions of greater than 6 months' duration [12] or where physical activity advice is combined with dietary advice [13]. Significant improvements in levels of physical activity have been demonstrated via the use of one-to-one physical activity consultations [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a majority of patients seem to prefer psychological treatment to pharmacotherapy for mental disorders [3,4]. Importantly, psychological interventions can be applied also to diseases and disorders that are common in healthcare but often difficult to medically manage [5][6][7].…”
Section: Introductionmentioning
confidence: 99%